PENGARUH STRATEGI BISNIS TERHADAP INOVASI PRODUK UMKM DENGAN AKUNTANSI MANAJEMEN LINGKUNGAN SEBAGAI VARIABEL INTERVENING - Widiarto, Ardian; Rusniti, Rusniti; Hasanudin, Mohamad; Kusuma, Septian Yudha (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
This study aims to determine the effect of business strategies carried out by food processing MSMEs in Semarang City on product innovation where environmental management accounting plays a role as an intervening variable. Environmental management accounting provides environmental cost information that can support decision-making related to environmental management. Determining the right business strategy can spur MSMEs to increase competitiveness through product innovation. Business strategies that consider ecological sustainability are an interesting issue today. Business strategies that prioritize environmental preservation will trigger product innovation that is highly competitive both nationally and internationally. The research method used is quantitative. This study uses a purposive sampling technique with criteria and considerations to determine the sample. Data collection was carried out by distributing questionnaires to food processing MSMEs in Semarang City and the final result was 100 respondents. SmartPLS 3 was used as a research instrument test tool. The results obtained are that Environmental Management Accounting plays a role in mediating the influence of Business Strategy on Product Innovation in a positive or strengthening direction